Dogs, zoonoses, and public health - Macpherson, C. N. L. (Calum N. L.); Meslin, F.-X. (Francois-X.); Wandeler, Alexander I. (CABI Pub., 2000)
Domestication of the dog some 14000 years ago has enabled this species to become the most abundant carnivore in the world today with an estimated population of 500 million. Dogs perform a wide range of roles from working as guides for the blind and deaf, guarding, protecting and driving sheep and cattle, and in hunting. Most, however, are companion animals, and the benefits of contact with animals to human health and psychological well-being is now well recognised. As well as the advantages, the close relationship between dogs and humans brings its problems. Zoonotic diseases such as rabies and a wide range of helminth and protozoal parasites represent a threat to public health. This threat of zoonotic infection is greatest for immunosuppressed people such as those with AIDS or malnutrition, or those under immunosuppressive medication for cancer and transplant therapy. This book aims to provide a comprehensive account of the interaction between dogs and humans in various social and cultural situations throughout the world. The chapters are written by 22 contributors from all over the world and the first two chapters cover the human-canine relationship (including the social and health benefits of dogs and their use in therapy) and dog ecology and population biology. Then follow chapters on rabies, bacterial zoonoses, protozoal zoonoses, trematodes, cestodes, nematodes and ectoparasites. The final three chapters cover zoonoses and immunosuppressed populations (immunosuppressed dogs as well as humans), management of dog populations (including legislation, education and costs), and control of zoonoses in dogs (using rabies, leishmaniasis and echinococcosis as examples). The chapters are supported by references and there is a subject index.